Evaluation of Common bean (Phaseolus vulgaris) Genotypes for their Yield and Adaptability in Amhara Regional State, Ethiopia - Kefelegn, Nigusie (Madda Walabu University Journal of Equity in Sciences and Sustainable Development, 2019)
Considering the lack of improved varieties as a major problem in common bean production in Amhara region, an experiment was conducted to select high yielder and stable genotype/s. The experiment was done in 2011 and 2012 at Sirinka, Kobo, Jari and Shewarobit. Ten genotypes including the check were evaluated in randomized complete block design. The analysis of variance showed that there is high significant interaction of genotype by location by year which can need further analysis using AMMI model. In the AMMI, the first two interaction principal component analysis accounted for 71.6% for the total interaction and MR 14000-2-10P and MR 14195-13-4P with yield 1.75 and 1.73 t ha-1, have low IPCA scores and AMMI stability value. Thought, its IPCA scores and AMMI stability value are high, genotype MR 14152-43-2P ranked first in its seed yield (2.2 t ha-1,) in all environments except Shewarobit 2012. Overall, MR 14152-43-2P is found best genotype and can increase productivity and production in common bean growing areas of Amhara and it was released with vernacular name Fetene.